HPV vaccination and Native Americans: protocol for a systematic review of factors associated with HPV vaccine uptake among American Indians and Alaska Natives in the USA. Issue 9 (6th September 2020) - Gopalani, Sameer Vali; Sedani, Ami E; Janitz, Amanda E; Clifton, Shari C; Stoner, Julie; Peck, Jennifer; Comiford, Ashley; Salvatore, Alicia L; Campbell, Janis
Abstract : Introduction: The nine-valent human papillomavirus (HPV) vaccine could prevent an estimated 92% of the cancers attributable to HPV types targeted by the vaccine. However, uptake of the HPV vaccine among American Indian and Alaska Native (AI/AN) adolescents has been low. AI/ANs also bear a disproportionate burden of cervical and other HPV-associated cancers. Increasing HPV vaccination rates is a national priority, but reviews and national surveys on HPV vaccination factors are lacking for the AI/AN population. The objective of this systematic review is to assess factors associated with HPV vaccination among AI/ANs in the USA. Methods and analysis: A systematic review is proposed to synthesise the current literature on HPV vaccination factors in AI/ANs from 1 July 2006 until 30 September 2019. As applicable, controlled vocabulary terms, keywords and special features (eg, limits, explode and focus) will be incorporated into database searches. To maximise the identification of relevant studies, citation indexes and databases that index dissertations, preprints and grey literature are included. Studies will be screened and selected independently in two stages. In stage 1, titles and abstracts will be screened. In stage 2, full-text articles will be screened and selected. A data extraction form and quality assessment tool will be piloted, revised and implemented. If available, measures of frequency and association will be presented. A narrative synthesis of the included studies will also be undertaken and reported. Ethics and dissemination: As our review will use publicly available data and publications, an Institutional Review Board review will not be required. We will disseminate the findings from this review through peer-reviewed publication(s) and conference presentation(s). Potential amendments: In the event of amendments to the protocol, we will provide the date, rationale, and description of the change for each amendment. PROSPERO registration number: CRD42020156865.